Plantar Pressure Distribution Patterns of Individuals with Prediabetes in Comparison with Healthy Individuals and Individuals with Diabetes. (September 2013) - Robinson, Caroline Cabral; Balbinot, Luciane Fachin; Silva, Marcelo Faria; Achaval, Matilde; Zaro, Milton Antônio
Background: Since elevated mechanical stress along with loss of plantar protective sensation are considered relevant factors in skin breakdown resulting in diabetic foot ulcerations, the assessment of plantar pressure is important for the prevention of diabetic foot complications. Prediabetes subjects are at risk of chronic hyperglycemia complications, among them neuropathy, but information about plantar loading in this population is not available. We aimed to compare baropodometric parameters of individuals with prediabetes versus healthy persons and persons with diabetes mellitus (DM). Methods: Baropodometric data from 73 subjects (15 with prediabetes (pre-DM), 28 with type 2 DM, 30 healthy) aged between 29 and 69 years of both genders were registered through a pressure platform with self-selected gait speed and first-step protocol. Peak plantar pressure, stance time, percentage of contact time, percentage of contact area and pressure-time integral were assessed in five plantar foot regions: Heel, midfoot, metatarsals, hallux, and toes 2 to 5. Groups were compared by one-way analysis of variance with Scheffé post hoc (α = 0.05). Results: Age, body mass index, gender, and arch height index did not differ between groups. Pre-DM and DM subjects presented increased peak pressure and pressure-time integral in metatarsals ( p = .010; p > .001), as well as increased percentage of contact time in midfoot ( p = .006) and metatarsals ( p = .004) regions when compared with healthy subjects. Stance time was significantly higher ( p = .017) in DM subjects. Conclusions: Pre-DM subjects seem to exhibit an altered plantar pressure distribution pattern similar to that often found in DM subjects.